Network meta-analysis: efficacy of treatment for acute, chronic, and prevention of pouchitis in ulcerative colitis. Issue 5 (9th March 2022) - Poo, Stephanie; Sriranganathan, Danujan; Segal, Jonathan P
Abstract : Introduction: Pouchitis is a clinically significant complication of ileal pouch-anal anastomosis. There is a paucity of head-to-head comparisons between treatments and no data were available about how each treatment rank against each other. A network meta-analysis of the different treatments used for acute, chronic and prevention of pouchitis was conducted. Methods: Biomedical databases and the Cochrane Central registry were searched between 1978 and 2021 for randomised controlled trials examining treatment for acute, chronic and prevention of pouchitis. A network meta-analysis was performed using the frequentist model with pooled relative risks and P scores used to rank treatments. Results: 18 studies were included from a screen of 4291 abstracts. When compared to placebo, rifaximin was found to be the best antibiotic for acute pouchitis whereas ciprofloxacin ranked highest against metronidazole. For chronic pouchitis, metronidazole followed by probiotics was statistically significant and effective treatments in inducing remission although metronidazole had the highest adverse events. Adalimumab and bismuth were also found to be superior to placebo; however, they did not reach statistical significance. Probiotics proved superior to placebo in the prevention of pouchitis development. Conclusions: This is the first network meta-analysis which compares the efficacy and tolerability of treatments in the management and prevention of acute and chronic pouchitis. It confirms that antimicrobial therapy remains the mainstay of treatment and adds weight to current guideline recommendations. Our results demonstrate that rifaximin and probiotics may deserve a more prominent role. While biologics are starting to show promise, large-scale head-to-head comparisons are warranted to validate the efficacy of these treatments.